2021
DOI: 10.1186/s12912-021-00627-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of clinical competence – a longitudinal survey of nurse practitioner students

Abstract: Background In order to achieve a sustainable standard of advanced clinical competence for nurse practitioners leading to a credible role, it is important to investigate the development of clinical competence among nurse practitioner students. Aim The aim of the present study is to analyse the development of nurse practitioner students’ self-assessed clinical competence from the beginning of their education to after completion of their clinical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
2
16
0
1
Order By: Relevance
“…Another study found that the greatest development of competence was in relation to direct clinical practice. Although the students entered the program with different levels of competence, this was largely equalized during their education in the master’s program [ 26 ]. The data from the focus group in our study showed that the learning outcomes from the VRGs strengthened the students’ critical thinking skills in the process of developing their competence, in particular by taking increased responsibility for leading professional discussions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that the greatest development of competence was in relation to direct clinical practice. Although the students entered the program with different levels of competence, this was largely equalized during their education in the master’s program [ 26 ]. The data from the focus group in our study showed that the learning outcomes from the VRGs strengthened the students’ critical thinking skills in the process of developing their competence, in particular by taking increased responsibility for leading professional discussions.…”
Section: Discussionmentioning
confidence: 99%
“…APN students also need to learn medical subjects while maintaining a holistic approach that includes providing patient-centered care, which is the foundation of nursing [ 7 ]. Developing clinical decision-making is another important aspect of clinical competence [ 26 , 27 ]. APNs are experts in nursing who have extended their medical knowledge while retaining their unique nursing character [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The problem that drove the research study was the ambiguous and unclear meaning of clinical learning opportunity that created challenges and uncertainties for nurse educators, CETU personnel and operational managers in the clinical areas. The student nurses were not provided with sufficient CLOs and practical experiences to meet their clinical learning goals (Mothiba et al 2020;Motsaanaka et al 2020;Taylor et al 2021). The uncertainties and challenges led to the poor professional development of the student nurses (Berhe & Gebretensaye 2021).…”
Section: Research Methods and Designmentioning
confidence: 99%
“…Furthermore, student nurses became despondent and demotivated, leading to frustration, increased absenteeism and prolonged length of study due to inadequate CLOs (Berhe & Gebretensaye 2021;Motsaanaka et al 2020). Exposure to real-life practice settings, experiences and clinical activities provides opportunities that will facilitate clinical learning to bridge the gap between theory and practice and prepare the student nurses to develop the qualifications of a clinically competent, independent, professional nurse practitioner (Taylor et al 2021;Zulu, Du Plessis & Koen 2021). Motsaanaka et al (2020) also report that clinical exposure to learning opportunities will develop the student nurses' clinical competencies in higher-order thinking skills (HOTS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation